Antimicrobial potential of toothpaste formulated from extracts of Syzygium aromaticum, Dennettia tripetala and Jatropha curcas latex against some oral pathogenic microorganisms - Olugbenga Oludayo Oluwasina; Ifunanya Vivian Ezenwosu; Clement Olusola Ogidi; Victor Olusegun Oyetayo (AMB Express, 2019)
Abstract The need for a broad spectrum antimicrobial mouthwash is highly desirable to reduce, control and prevent various types of dental diseases. Hence, research into the production of herbal toothpaste to suppress the incidence of dental diseases is pertinent. The present study formulated herbal toothpastes from edible and medicinal plants namely; Syzygium aromaticum, Dennettia tripetala, and Jatropha curcas latex. The antimicrobial activity of the toothpastes was assessed against some oral pathogenic microorganisms using agar well diffusion. Phytochemical analysis of S. aromaticum and D. tripetala revealed the presence of phenols, flavonoids, alkaloid, and saponins. The major constituent of the plants from gas chromatography mass spectrometer (GC/MS) analysis are eugenol (83.58%), caryophyllene (4.35%) and phenol, 2-methoxy-4-(2-propenyl)-, acetate (12.07%) from S. aromaticum, while D. tripetala had glutaric acid (57.57%), eugenol (2.9%), caryophyllene (1.12%), and 1,6,10-dodecatrien-3-ol, 3,7,11-trimethyl-,(E)- (3.36%). The pH and specific gravity of the formulated toothpastes respectively ranged from 8.57 to 9.67 and 1.08 to 1.10, while the pH and specific gravity of commercial toothpastes were from 5.39 to 8.55 and 0.97 to 1. 11 respectively. The formulated toothpastes have better and significant (P < 0.05) antimicrobial effect when compared to commercial toothpastes. The zones of inhibition of formulated toothpastes against the tested microorganisms ranged from 4.0 to 18.30 mm, while MIC ranged from 2.5 to 20.0 mg/mL. The formulated toothpastes exhibited potent antimicrobial property against the tested pathogens as a result of bioactive compounds in them. Hence, these biomolecules can be extracted for the production of safe and effective herbal-based toothpaste.